Generation Z And Sharia Finance: UIN Ar-Raniry Students' Perceptions Of Bank Indonesia's Savings Products - Isnaliana, Isnaliana; Tarigan, Ismail Rasyid Ridla; Maulana, Andri (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2025)
In the current digital era, students are increasingly dependent on Islamic bank savings products to meet their daily transaction needs. Although in general students are satisfied with one savings product, dissatisfaction with the product they have encourages them to open an account at another sharia bank. This shows that product and service quality is the main factor in choosing savings products for students. The aim of this research is to determine the perceptions of students at the Islamic Economics and Business Faculty of UIN Ar-Raniry towards Bank Syariah Indonesia savings products. This research method uses qualitative, with interview and documentation techniques. The results of the perception research are based on three aspects: 1) The assessment aspect, some students gave an assessment while using Bank Syariah Indonesia's savings products as very good. 2) In the response aspect, the majority of students agree and are greatly helped by the presence of Bank Syariah Indonesia savings products in the student environment. 3) Opinion aspect, all students stated that Bank Syariah Indonesia's savings products were very relevant to what was needed, both internal and external needs.